国際極年中にEISCATスバールバルレーダーで観測された高強度のプラズマライン - 佐藤, 由佳; 小川, 泰信; Nickolay, Ivchenko; Nicola, M. Schlatter; Yuka, Sato; Yasunobu, Ogawa (2017)
第8回極域科学シンポジウム/個別セッション：[OS] 宙空圏 12月5日（火）統計数理研究所 3階セミナー室D304 The Eighth Symposium on Polar Science/Ordinary sessions: [OS] Space and upper-atmosphere sciences Tue. 5 Dec./3F Seminar room D304, Institute of Statistics and Mathematics conference object